This is our rainbow : 16 stories of her, him, them, and us - Locke, Katherine; Melleby, Nicole (Alfred A. Knopf, 2021)
Contains a collection of LGBTQA+ short stories for middle schoolers about the themes of identity, love, family, and friends.